2007
DOI: 10.1103/physrevb.75.165206
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality-dependent energy transfer in polymer-intercalatedSnS2nanocomposites

Abstract: We have investigated the influence of dimensionality on the excitation-transfer dynamics in a conjugated polymer blend. Using time-resolved photoluminescence spectroscopy, we have measured the transfer transients for both a three-dimensional blend film and for quasi-two-dimensional monolayers formed through intercalation of the polymer blend between the crystal planes of an inorganic SnS 2 matrix. We compare the experimental data with a simple, dimensionality-dependent model based on electronic coupling betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…α indicates the dimensionality and diffusion dynamics in the density of states of energy transfer [97]. For single step three dimensional FRET, α = 1 / 2, for single step two-dimensional FRET α = 1 / 3 [98] and for diffusive transport only (followed by a final nearest neighbour hop into the acceptor) α = 1 for a simple random walk. In the case of diffusive transport in an inhomogenously broadened density of states [95] α is slightly less than 1 since diffusion slows down with time due to energy relaxation [99].…”
Section: Exciton Harvestingmentioning
confidence: 99%
“…α indicates the dimensionality and diffusion dynamics in the density of states of energy transfer [97]. For single step three dimensional FRET, α = 1 / 2, for single step two-dimensional FRET α = 1 / 3 [98] and for diffusive transport only (followed by a final nearest neighbour hop into the acceptor) α = 1 for a simple random walk. In the case of diffusive transport in an inhomogenously broadened density of states [95] α is slightly less than 1 since diffusion slows down with time due to energy relaxation [99].…”
Section: Exciton Harvestingmentioning
confidence: 99%
“…[1,[6][7][8] Recently, it was shown that energy transfer in conjugated polymers has strong dependence on dimensionality, with much slower transfer in 1D and 2D systems, in which neighboring polymer chains are weakly or not coupled, compared to 3D films. [9][10][11][12] The slower energy transfer in the low-dimensional systems, that is, polymer monolayers (2D) and isolated polymer chains (1D), was attributed to the absence of the strong chain coupling present in 3D films. The absence of the closely p-p packed polymer chains, known to be the origin of fast energy transfer in 3D films, suppresses the overall rate of energy transfer in the low-dimensional systems.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of the closely p-p packed polymer chains, known to be the origin of fast energy transfer in 3D films, suppresses the overall rate of energy transfer in the low-dimensional systems. [10,12] Recently, stalled energy transfer in 2D systems was utilized for the fabrication of color-controlled [13] and white-emitting PLEDs. [13,14] However, whether 2D energy transfer in conjugated polymer monolayers occurs mainly along polymer chains (intrachain) or between in-plain neighboring but noncoupled polymer chains (interchain) has yet to be determined due to the experimental difficulty of decoupling inter-and intrachain interactions in polymer monolayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each single H‐slab layer consists of one layer occupied only by metal atoms on both sides confined by sulphur. Since the binding forces between both slabs are weak the intercalation of additional metal atoms or polymers is possible between them 53–55. Hence, the H‐slab acts as host compound.…”
Section: Structurally Cylindrite Belongs To the Misfit Layer Compomentioning
confidence: 99%